WAYS TO ENSURE SECURITY IN COMMERCIAL BANKS (Spectrum Journal of Innovation, Reforms and Development, 2022)
In the article, proposals and recommendations on the nature of digital banking in the national economy, its application, current state and development analysis are considered. Also, features of digital banking development in commercial banks were considered.